APPLICATION OF NEW LABORATORY METHODS IN DIFFERENTIAL DIAGNOSIS OF CHRONIC CHLAMYDIA AND MYCOPLASMAL PNEUMONIA WITH PULMONARY TUBERCULOSIS (World Bulletin of Public Health, 2024)
It is generally recognized that in recent years the role of chlamydia and mycoplasmas in the respiratory pathology of adults and older children has increased markedly, but information on their importance in children of the first years of life is quite contradictory. Thus, according to K.A.Okhlopkova 2008, Chlamydophila pneumoniae, which is associated with 24.7%, and mycoplasma pneumonia in 13.2% of community-acquired lower respiratory tract infections, currently has a dominant role in the structure of respiratory chlamydia in hospitalized young patients. Approximately one third of these cases are due to chronic forms of infection
Keywords: Human immunodeficiency virus; World Health Organization; medical and labor expert commission